CONTRIBUTION TO THE DETERMINATION OF THE OPTIMAL PLOUGHING DEPTH ON TROPICAL FERRUGINOUS SOIL IN NORTHERN BENIN: IMPACT ON SOIL STRUCTURE AND YIELD OF A CORN CULTURE. - ZOKPODO, KOESSI LIÈ BARNABÉ (My University, 2017)
Effects of three different types of ploughing (light, middle and deep) on physical parameters of a tropical ferruginous soil of the Northern Benin, and their consequences on the growth and grain yield of two varieties of maize has been examined. The ploughing was achieved with a disk plow and the other cultural operations achieved manually. Results showed that tillage to important depth manipulates important quantity of soil, what makes it vulnerable to the deterioration. The impact of the ploughing depths was very important on the crumbling of soil, the profusion and especially the infiltration of water. Two varieties of corn TZEE-W-SR and DMR-ESR-WS have been experimented to the different depths of ploughing. The cultures showed a better vegetative development and an optimal output around 20 cm depth of ploughing.
Keywords: Motorized ploughing; structure of soil; depth of ploughing; agricultural output; Benin